POSITIVE LEADERSHIP MODELS: THEORETICAL FRAMEWORK AND RESEARCH - Javier Blanch, Francisco Gil; Mirko Antino; Alfredo Rodríguez-Muñoz (Papeles del Psicólogo, 2016)
The objective of this article is twofold; firstly, we establish the theoretical boundaries of positive leadership and the reasons for its emergence. It is related to the new paradigm of positive psychology that has recently been shaping the scope of organizational knowledge. This conceptual framework has triggered the development of the various forms of positive leadership (i.e. transformational, servant, spiritual, authentic, and positive). Although the construct does not seem univocally defined, these different types of leadership overlap and share a significant affinity. Secondly, we review the empirical evidence that shows the impact of positive leadership in organizations and we highlight the positive relationship between these forms of leadership and key positive organizational variables. Lastly, we analyse future research areas in order to further develop this concept.